Änderung des Wirtswahlverhaltens dreier Biotypen von Acyrthosiphon pisum (Harris) nach Anzucht auf verschiedenen Wirtspflanzen (Homoptera: Aphididae). - Hubert-Dahl, Maria Luise (Contributions to Entomology = Beiträge zur Entomologie, 1975)
In cage experiments adult viviparae of a green and a red biotype of Acyrthosiphon pisum (Harris) were allowed to settle by choice on Vicia faba L., Vicia villosa Roth, Pisum sativum L., Trifolium pratense L. and Medicago sativa L. The principal host plants of the green form are Vicia villosa and Pisum sativum, the red form on the other hand is restricted to Trifolium pratense. Both biotypes, however, can reared successfully on Vicia faba. Aphids taken from stock cultures on Vicia faba settled on this plant to a higher percentage compared with aphids of the same biotypes after rearing for 1-2 generations on Vicia villosa or Trifolium pratense respectively. Apterous viviparous females of another red biotype, which prefers Medicago sativa as host and which settles also on Trifolium pratense indicated after rearing on Trifolium pratense a somewhat increased colonization on red clover in comparison with those that had developed on alfalfa. Feeding on red clover for one generation caused the same increase of the colonization on Trifolium pratense as a rearing period of 26 months on this plant.